Paradigma dan Karakteristik Sistem Ekonomi Islam: Kajian Teoretis dan Filosofis: Paradigms and Characteristics of the Islamic Economic System: A Theoretical and Philosophical Study - Desy Arum Sunarta; Nelia Syafriawati; Mukhtar Lutfi (HISAB: Jurnal Akuntansi Lembaga Keuangan Syariah, 2025)
This study aims to provide a comprehensive understanding of the paradigm and characteristics of the Islamic economic system as an alternative to the conventional economic system that is oriented toward materialism and market efficiency. The research employs a descriptive qualitative method using a library research approach through content analysis to identify core values and principles, comparative analysis to distinguish Islamic economics from conventional systems, and descriptive–qualitative analysis to explain its implementation in modern economic practices. The findings show that the Islamic economic system is a framework that places divine values and sharia principles as the main foundation of economic activity in order to achieve falah in this world and the hereafter. Islamic economics offers a balanced approach between individual ownership and social interests, making it an alternative solution that integrates economic growth with equitable welfare distribution. In the contemporary context, the application of the Islamic economic paradigm can be seen in the development of Islamic finance, the halal industry, productive zakat, and social waqf, which have become increasingly relevant in addressing the challenges of globalization. Thus, Islamic economics has the potential to become an economic model that is just, ethical, and sustainable.